Implementasi Algoritma SIFT (Scale-Invariant Feature Transform) Dan Algoritma Kalman Filter Dalam Mendeteksi Objek Bola - saputra, chindra (Jurnal PROCESSOR, 2023)
The Indonesian Football Robot Contest (KRSBI) is a division of the Indonesian Robot Contest (KRI) which is held annually by RISTEKDIKTI and KEMENDIKBUD. In a soccer robot contest, the robot is required to detect the ball and then lead it to the opponent's goal so that a goal can be created. a good object detection system must be fast, light, and of course it must have good accuracy. Currently, the object detection system that has been applied to robots is in the form of color filtering which is considered quite good in detecting an object. However, if you only rely on this method, it is still lacking when viewed from the point of view of object tracking. The Kalman Filter algorithm serves as an estimator that can be used to predict the direction of movement of an object based on the object's status from the previous frame. This allows the robot to move 1 (one) frame faster than the object to be tracked. The SIFT algorithm can compare two images through the features of the image and produce whether the images are similar or not. This algorithm is useful for ascertaining whether the object detected by the robot is a ball or not. This research combines the SIFT and Kalmal Fiter algorithms to produce a better detection system than before. It is hoped that the results of this research can be used by robots in participating in the Indonesian soccer robot contest.